1995
DOI: 10.1161/01.hyp.25.6.1191
|View full text |Cite
|
Sign up to set email alerts
|

Antihypertensive Effects of a Novel Endothelin-A Receptor Antagonist in Rats

Abstract: Endothelin is a potent pressor agent mediated primarily through activation of endothelin-A receptors on vascular smooth muscle. Surprisingly, there is no consensus in the literature regarding the role of endothelin itself or endothelin-A receptors in hypertension. The goal of this study was to compare the effects of the novel, selective endothelin-A receptor antagonist BMS-182874 in various models of hypertension. BMS-182874 specifically inhibited the pressor response to endothelin-1 (0.3 nmol/kg IV) in Spragu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
31
0

Year Published

1997
1997
2008
2008

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(33 citation statements)
references
References 17 publications
2
31
0
Order By: Relevance
“…Consistent with the actions of AT 1 receptor Sprague-Dawley rats treated with DOCA and drinking 0.9% NaCl (DOCA-salt rats) develop hypertension that is associated with a suppression of the renin-angiotensin system and increased tissue levels of ET-1 (Fujita et al, 1995;Schiffrin et al, 1996). Consequently, ET A receptor antagonists (Bird et al, 1995;Schiffrin et al, 1997) but not AT 1 receptor antagonists (Wada et al, 1995;Pollock et al, 2000) have shown antihypertensive activity in this model. Compounds A and C reduced blood pressure in hypertensive DOCA-salt rats, consistent with the actions of an ET A receptor antagonist.…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…Consistent with the actions of AT 1 receptor Sprague-Dawley rats treated with DOCA and drinking 0.9% NaCl (DOCA-salt rats) develop hypertension that is associated with a suppression of the renin-angiotensin system and increased tissue levels of ET-1 (Fujita et al, 1995;Schiffrin et al, 1996). Consequently, ET A receptor antagonists (Bird et al, 1995;Schiffrin et al, 1997) but not AT 1 receptor antagonists (Wada et al, 1995;Pollock et al, 2000) have shown antihypertensive activity in this model. Compounds A and C reduced blood pressure in hypertensive DOCA-salt rats, consistent with the actions of an ET A receptor antagonist.…”
Section: Discussionmentioning
confidence: 89%
“…This study was performed as described previously (Bird et al, 1995). Sprague-Dawley rats were prepared as described above.…”
Section: Radioligand Binding Studiesmentioning
confidence: 99%
“…Selective ET A antagonists such as BQ 123, BMS 182874 and FR 139317 block the rise of BP in certain rat models, which shows that hypertension is to some extent dependent on endothelin-related mechanisms. 7,26,27 Selective ET A receptor antagonists significantly reduce BP in hypertensive subjects. 28,29 ET A receptor antagonists cause a greater degree of vasodilatation in forearm vessels of essential hypertensive patients than in normotensive controls, suggesting a predominant role of ET A receptors in the regulation of vascular tone by endogenous ET-1 in hypertension.…”
Section: Discussionmentioning
confidence: 99%
“…As an example, the combined ET A /ET B receptor antagonist bosentan produced minor changes on elevated MABP and vascular hypertrophy in deoxycorticosterone acetate-salt hypertensive rats (Li et al, 1994), whereas it did not modify MABP in spontaneously hypertensive rats (Li and Schiffrin, 1995). Administration of another orally active ET A receptor antagonist showed a similar discrepancy of effect between the two models (Bird et al, 1995). Thus, ET A receptor antagonism was active in abrogating the marked cardiovascular alterations produced by prednisolone.…”
Section: Nitro-prednisolone Does Not Cause Hypertension 1137mentioning
confidence: 94%